Influence of Replacement of Concentrate by Beer By-product on Performance of Broilers in Central Vietnam - Nguyen, L.Q.; Vui, T.Q.; Hue, H.T.; Hang, D.T.; Beynen, A.C. (International Journal of Poultry Science, 2004)
In an attempt to lower feed costs of small-holder broiler production in the area of Hue City, Central Vietnam, we replaced part of the commercial concentrate component of the diet by locally available wheat brewing by-product. There were three experimental diets containing either 5, 10 or 15% brewing by-product. The three diets were fed on five small-holder farms to groups of 20 broilers each. The results show that beer by-product enhanced growth and improved feed efficiency. Slaughter carcass traits and the weights of breast and drumstick were enhanced by the feeding of beer by-product. The inclusion of 10% beer by-product in the diet increased the antibody titre against Newcastle disease when the birds were aged 9 weeks, but not when they were aged either 4 or 12 weeks. It is concluded that substitution of brewers` wheat for part of the concentrate component can render broiler diets less expense and more efficient.